Connecting remote and in situ observations of shock-accelerated electrons associated with a coronal mass ejection - Morosan, D. (EDP Sciences, 2025)
Context. One of the most prominent sources for energetic particles in our Solar System are huge eruptions of magnetised plasma from the Sun, known as coronal mass ejections (CMEs), which usually drive shocks that accelerate charged particles up to relativistic energies. In particular, energetic electron beams can generate radio bursts through the plasma emission mechanism, for example, type II and accompanying herringbone bursts.
Aims. In this work, we investigate the acceleration location, escape, and propagation directions of various electron beams in the solar corona and compare them to the arrival of electrons at spacecraft. Methods. To track energetic electron beams, we used a synthesis of remote and direct observations combined with coronal modeling. Remote observations include ground-based radio observations from the Nançay Radioheliograph (NRH) combined with space-based extreme-ultraviolet and white-light observations from Solar Dynamics Observatory (SDO), Solar Terrestrial Relations Observatory (STEREO), and Solar Orbiter (SolO). We also used direct observations of energetic electrons from the STEREO and Wind spacecraft. These observations were then combined with a three-dimensional (3D) representation of the electron acceleration locations, including the results of magneto-hydrodynamic models of the solar corona. This representation was subsequently used to investigate the origin of electrons observed remotely at the Sun and their link to in situ electrons.
Results. We observed a type II radio burst followed by herringbone bursts that show single-frequency movement through time in NRH images. The movement of the type II burst and herringbone radio sources seems to be influenced by regions in the corona where the CME is more capable of driving a shock. We found two clear distinct regions where electrons are accelerated in the low corona and we found spectral differences between the radio emission generated in these regions. We also found similar inferred injection times of near-relativistic electrons at spacecraft to the emission time of the type II and herringbone bursts. However, only the herringbone bursts propagate in a direction where the shock encounters open magnetic field lines that are likely to be magnetically connected to the same spacecraft.
Conclusions. Our results indicate that if the in situ electrons are indeed shock-accelerated, the most likely origin of the in situ electrons arriving first is located near the acceleration site of herringbone electrons. This is the only region during the early evolution of the shock where there is clear evidence of electron acceleration and an intersection of the shock with open field lines, which can be directly connected to the observing spacecraft. © The Authors 2024.